Statistical sound evaluation for the improvement of sound insulation systems - OHTA, Mitsuo; IWASHIGE, Hirofumi (Archives of Acoustics, 1988)
The random noise fluctuation encountered in our living environment, such as street noise, road traffic noise, etc. exhibits various kinds of probability distribution forms apart from the usual Gaussian distribution due to the diversified causes of the fluctuations. From the practical viewpoint of control and regulation of such environmental noise, several statistics, such as median, L_5 and L_10 (in general, so called L_α sound level), directly connected with the probability distribution form of random noise fluctuation are very often used for evaluation of the human response. Thus, it is essential to establish a systematic method for evaluating the effect of the system change of noise control on the widely-used standard noise index such as L_α. In this paper, general and fundamental considerations for statistical evaluation of transmitted sound waves have been theoretically proposed, when the system characteristic of the sound insulation is changed by any improvement work. The theoretical result was experimentally confirmed not only by the result of the digital simulation technique, but also by actually observed data obtained using reverberation room method. The results of the experiment are in good agreement with our theory.